2021
DOI: 10.22141/2308-2097.51.2.2017.101706
|View full text |Cite
|
Sign up to set email alerts
|

Актуальність Визначення Спектра Жирних Кислот У Біологічних Субстратах У Діагностиці Гастроентерологічних Захворювань

Abstract: Резюме. У статті розглянуто роль вільних жирних кислот у патогенезі метаболічних і гастроентерологічних захворювань. Обґрунтовано доцільність використання методу газової хроматографії для визначення жирнокислотного складу біологічних рідин (сироватка крові, сеча, кал тощо). Показано, що вільні жирні кислоти беруть участь у формуванні структурних компонентів клітин, енергетичному гомеостазі й виконують роль сигнальних молекул або їх попередників, тому порушення регуляції метаболізму жирних кислот може призвести… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(11 reference statements)
0
2
0
1
Order By: Relevance
“…Lipids are usually deposited in adipose tissue (AT), but numerous studies have also shown that AT is involved in the regulation of metabolic processes through the control of the level of lipids and free fatty acids (FFA) in the blood plasma. More and more evidence are emerging to support the concept that peptides and hormones produced in AT are an important component of endocrine regulation of homeostasis of carbohydrates and lipids [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids are usually deposited in adipose tissue (AT), but numerous studies have also shown that AT is involved in the regulation of metabolic processes through the control of the level of lipids and free fatty acids (FFA) in the blood plasma. More and more evidence are emerging to support the concept that peptides and hormones produced in AT are an important component of endocrine regulation of homeostasis of carbohydrates and lipids [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This allows early detection of systemic disorders and diseases associated with lipid imbalance and hence improve the quality of treatment. Many researchers emphasize the importance of studying certain types of FAs as biological markers of metabolic homeostasis disorders and early detection of pathological conditions in the body [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Перевага цього методу полягає у швидкості виконання й високій чутливості методу, завдяки чому можливо виявити найменші концентрації сполук у дослідному зразку (до 10 -12 моль). Впровадження цього методу в клінічну практику лікарів дозволяє діагностувати захворювання печінки на ранньому етапі розвитку та коригувати виявлені порушення [11].…”
Section: вступunclassified